Hubungan Intensitas Penggunaa Gadget Dengan Sikap Sosial Siswa Dalam Pembelajaran IPAS Kelas IV SD Negeri 01 Koto Nan IV Tarusan Sumatera Barat: Intensitas Penggunaa Gadget - Tamrin, M; Qory, Qorry Yolly Sahrani (Yayasan Insan Cipta Medan, 2025)
ABSTRACT This study was motivated by the high level of gadget use among elementary school students which has the potential to affect the development of their social attitudes. The purpose of this research was to determine the relationship between the intensity of gadget use and students' social attitudes in Science and Social Studies (IPAS) learning in Grade IV at SD Negeri 01 Koto Nan IV. The type of research used was quantitative research with a correlational approach. The population of this study consisted of all fourth-grade students at SD Negeri 01 Koto Nan IV. The sampling technique used was total sampling, so all fourth-grade students were used as research samples. The research data were collected using a questionnaire on the intensity of gadget use and a questionnaire on students’ social attitudes. Data analysis was carried out using a correlation test to determine the relationship between the two variables. The results showed that there is a relationship between the intensity of gadget use and students’ social attitudes in IPAS learning. The higher the intensity of gadget use, the greater the tendency for students’ social attitudes in direct interaction to decrease. Therefore, the use of gadgets needs to be directed and supervised wisely so that it does not hinder the development of students' social attitudes during the learning process.